Fluid dynamics and computational modeling - Forest, Maria, author (New York : Clanrye Intl., 2014)
This book contains updated information on topics like fluid dynamics, computational modeling and its applications, and aims to help scientists, engineers, and graduate students as a general reference. It discusses topics like: winds, building and risk prevention; multiphase flow, structures and gases; heat transfer, combustion and energy; medical and biomechanical applications; and other crucial topics. Along with all that has been mentioned, this book also gives a detailed view of computational fluid dynamics and applications, without excluding experimental and theoretical aspects.